The impact of fiscal austerity on suicide mortality: Evidence across the 'Eurozone periphery'. (November 2015) - Antonakakis, Nikolaos; Collins, Alan
Abstract: While linkages between some macroeconomic phenomena and suicides in some countries have been explored, only two studies, hitherto, have established a causal relationship between fiscal austerity and suicide, albeit in a single country. The aim of this study is to provide the first systematic multiple–country evidence of a causal relationship of fiscal austerity on time–, gender–, and age–specific suicide mortality across five Eurozone peripheral countries, namely Greece, Ireland, Italy, Portugal and Spain over the period 1968–2012, while controlling for various socioeconomic differences. The impact of fiscal adjustments is found to be gender–, age– and time–specific. Specifically, fiscal austerity has short–, medium– and long–run suicide increasing effects on the male population in the 65–89 age group. A 1% reduction in government spending is associated with a 1.38%, 2.42% and 3.32% increase in the short–, medium– and long–run, respectively, of male suicides rates in the 65–89 age group in the Eurozone periphery. These results are highly robust to alternative measures of fiscal austerity. Improved labour market institutions help mitigate the negative effects of fiscal austerity on suicide mortality. Highlights: We examine the impact of fiscal austerity (FA) on suicide mortality (SM) across the Eurozone periphery. We also control for various economic and socio-demographic differences across countries. The impact of fiscal austerity on SM is gender-, age- and time-specific, and robust to various proxies of FA. FA has short-, medium- and long-run suicide-increasing effects on males in the 65–89 age group. Improved labour market institutions can help mitigate the negative effects of FA on SM.